2012
DOI: 10.1007/s00216-012-5915-9
|View full text |Cite
|
Sign up to set email alerts
|

Hyphenated techniques as tools for speciation analysis of metal-based pharmaceuticals: developments and applications

Abstract: Method development and applications of hyphenated techniques as tools for speciation analysis of metal-based pharmaceuticals are summarized within this review. Advantages and limitations of the separation modes-high-performance liquid chromatography (HPLC), capillary electrophoresis (CE), and gas chromatography (GC)-as well as the detection modes-inductively coupled plasma-mass spectrometry (ICP-MS) and electrospray ionization-mass spectrometry (ESI-MS)-are discussed. ICP-MS detection is found to be advantageo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 177 publications
0
27
0
Order By: Relevance
“…Nevertheless, all species data will be lost during atomization in the ICP. An effective strategy to regain such information is the hyphenation of separation techniques with ICP [131]. Although reversed phase chromatography (RP-HPLC) accounts for only very little retention for polar compounds, Mazzucotelli et al [132] separated one contrast agent and several degradation products using RP-HPLC/ICP-MS.…”
Section: Speciation Of Gd-casmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, all species data will be lost during atomization in the ICP. An effective strategy to regain such information is the hyphenation of separation techniques with ICP [131]. Although reversed phase chromatography (RP-HPLC) accounts for only very little retention for polar compounds, Mazzucotelli et al [132] separated one contrast agent and several degradation products using RP-HPLC/ICP-MS.…”
Section: Speciation Of Gd-casmentioning
confidence: 99%
“…Moreover, size exclusion chromatography (SEC) was used with ICP-MS to separate free Gd 3+ from Gd complexes and Gd adducts; however, the size differences between the individual Gd chelates are too small for effective SEC separation [133,134]. Ion chromatography (IC) [131,135], time-resolved luminescence (TRL) detector [136], and direct fluorescence [137] are also utilized for the separation of Gd species. Künnemeyer et al [138] indicated a high separation efficiency of hydrophilic interaction chromatography (HILIC) for ionic and polar compounds by the determination of contrast agents in blood plasma using HILIC hyphenated to electrospray ionization mass spectrometry (ESI-MS).…”
Section: Speciation Of Gd-casmentioning
confidence: 99%
“…26 And the interactions of cisplatin with proteins and DNA have also been investigated using a great variety of analytical techniques. Those methods and techniques, used for quantitative studies also, include electronic, vibration, uorescence spectroscopy, circular dichroism spectroscopy, liquid scintillation counting, nuclear magnetic resonance spectroscopy, atomic absorption spectroscopy (AAS), atomic emission spectroscopy (AES), high performance liquid chromatography with ultraviolet-visible detection (HPLC-UV), 1 capillary electrophoresis-inductively coupled plasma-mass spectrometry, 27 size exclusion chromatography coupled with inductively coupled plasma mass spectrometry (SEC-ICPMS), 28 electrospray ionization mass spectrometry (ESI-MS), inductively coupled plasma mass spectrometry (ICP-MS) [29][30][31] and HPLC-ICP-MS. 32,33 Among those techniques, ICP-MS is the most sensitive and reliable one for the determination of cisplatin. However, ICP-MS with single mass spectrometry may not be capable of providing enough selectivity to eliminate the interference from endogenous and exogenous metal ions and polyatomic groups.…”
Section: -3mentioning
confidence: 99%
“…Such speciation analysis can be done with hyphenated systems, combining gas chromatography (GC), high -performance liquid chromatography (HPLC), and capillary electrophoresis (CE) with various mass spectrometry or spectroscopic methods. Such hyphenated techniques are tools for drug speciation analysis, and allow high elemental selectivity and high sensitivity, especially when targeting metals or metal-containing drugs [5].…”
mentioning
confidence: 99%